AI Revolutionizing HR: How Artificial Intelligence is Shaping Our Work - Ferils, Muh. (Penelitian dan Pengembangan Ilmu, 2024)
The integration of artificial intelligence (AI) in human resource management (HRM) has become an increasingly important topic in academic literature and business practice. The aim of this research is to investigate the impact of using AI in HRM as well as its implications for human resource management practices in various organizations. The research method used is a systematic literature review, which involves collecting, analyzing and synthesizing related articles from various recognized primary sources. The results of the discussion show that the integration of AI in HRM can increase operational efficiency, improve employee performance evaluations, and enrich employee experience through more responsive HR solutions. However, this research also identified a number of challenges, including the complexity of the HR phenomenon, the constraints of limited data, and related ethical and legal issues. The implication of this research is the need for adaptation and transformation in HR practices to face the ongoing digitalization era. HR professionals need to increase their understanding and skills in adopting AI technology while paying attention to ethical aspects and its impact on employees and the organization. Further research is needed to further explore the potential and limitations of AI in HRM and identify effective strategies for facing future challenges.